2015
DOI: 10.1111/cdoe.12199
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing in UK general dental practice: a cross‐sectional study

Abstract: A high level of inappropriate antibiotic prescribing was observed amongst the GDPs studied. Features of the healthcare environment, such as clinical time pressures, and patient-related characteristics, such as expectations for antibiotics and refusal of operative treatment, are associated with antibiotic prescribing in the absence of infection. Individuals responsible for the commissioning and delivery of dental services should seek to develop targeted interventions addressing these issues in order to ensure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
128
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(136 citation statements)
references
References 25 publications
6
128
0
2
Order By: Relevance
“…13, 20 For example, in a 2016 cross-sectional study analyzing antibiotic prescribing of 568 patients among general dentists, less than 20% of antibiotics were prescribed in situations consistent with clinical guidelines. 21 However, these issues are not limited to just the US and UK, inappropriate antibiotic prescribing practices among dentists is a worldwide problem. 22–24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13, 20 For example, in a 2016 cross-sectional study analyzing antibiotic prescribing of 568 patients among general dentists, less than 20% of antibiotics were prescribed in situations consistent with clinical guidelines. 21 However, these issues are not limited to just the US and UK, inappropriate antibiotic prescribing practices among dentists is a worldwide problem. 22–24 …”
Section: Discussionmentioning
confidence: 99%
“…16, 25 Other important factors include failure of previous operative treatment, shortage of clinical time, and patient pressure. 21, 26 …”
Section: Discussionmentioning
confidence: 99%
“…As it has been previously reported that patients prefer antibiotic treatment and are often unwilling to accept operative intervention [34], the rapid symptomatic improvement of ADI with parenteral therapy may bolster these preferences and influence convalescent healthcare choices. Our finding that over a third of study participants reported recurrent infections might be a reflection of this.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that the majority of these prescriptions are inappropriate (Cope et al . ).…”
Section: Introductionmentioning
confidence: 97%